An Analytical Review of the Influence of Regulatory and Supervisory Bodies on the Business of the Islamic Financial Institutions (IFIs) in Pakistan - Jan, Sahibzada Muhammad Wasim; Hassan Shakeel Shah; Ahmad Azam Bin Othman (Islamic Banking and Finance Review, 2021)
Islamic financial market in Pakistan comprises Islamic banking, Takaful and Islamic capital market. It is regulated and supervised by the State Bank of Pakistan (SBP) and the Securities and Exchange Commission of Pakistan (SECP). Despite the regulatory and supervisory mechanism crafted by these authorities, there are other institutions such as the Council of Islamic Ideology (CII), Federal Shariat Court (FSC) and international institutions such as the Accounting and Auditing Organization for Islamic Financial Institutions (AAOIFI) and Islamic Financial Services Board (IFSB) which intervene and influence the Islamic banking practices. Based on an analytical approach, the current study found an overlapping situation in the authority exercised by these bodies over the business of the IFIs in Pakistan. Hence, a distinctive regulatory authority based on an adequate legal foundation should be created to watch over the business of the IFIs in Pakistan. The supreme authority can be conferred to the Shariah Advisory Committee (SAC) of the SBP or to a separate body in the current judicial infrastructure of the country in order to overview, harmonize and resolve the issues related to the business of the IFIs.